2016
DOI: 10.1111/papr.12449
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Physical Activity Decline as a Mediator in the Relationship Between Pain Catastrophizing, Disability, and Quality of Life in Patients with Painful Diabetic Neuropathy

Abstract: Pain catastrophizing was associated with increased disability and decreased quality of life in patients with PDN. Also, it was associated with a perceived decline in physical activity, which had a mediating role in the association between catastrophizing and disability and quality of life, respectively. This study emphasizes the role of catastrophic thinking about pain and the experienced loss in daily activities due to PDN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 34 publications
4
37
1
1
Order By: Relevance
“…In our study, PDN was associated with a lower QoL (Geelen et al, 2017) and disability (Abbott et al, 2011). This sample of Dutch patients with PDN reported a mean QoL score comparable to other studies in patients with PDN (Currie et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, PDN was associated with a lower QoL (Geelen et al, 2017) and disability (Abbott et al, 2011). This sample of Dutch patients with PDN reported a mean QoL score comparable to other studies in patients with PDN (Currie et al, 2007).…”
Section: Discussionsupporting
confidence: 82%
“…Research in the current sample has shown that pain catastrophizing was associated with increased disability and decreased QoL in patients with PDN. Interestingly, pain catastrophizing was associated with the subjective feeling of loss of physical activities due to the pain, while it was not associated with the estimated actual level of activity (Geelen et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current study showing sex differences in the MetS, MVPA, and HRQOL relationship is a reasonable extension from published evidence. Another recent study, more similar to the current study, showed that PA was a significant mediator in the relationship between pain catastrophizing and quality of life [35]. Albeit, the main independent variable in this similar study was not MetS (it was pain catastrophizing), it does support the mediating role of PA when a debilitating illness leads to changes in HRQOL.…”
Section: Discussionsupporting
confidence: 51%
“…A recent study also showed that both EuroQol five dimensions (EQ-5D) and Short Form-6 dimension (SF-6D) questionnaires can discriminate between chronic pain with or without neuropathic pain 173 . Furthermore, the role of psychological factors in impairing quality of life in neuropathic pain has been analysed 174 , showing, for example, that pain catastrophizing was associated with decreased HRQOL 174 . The SF-36 and the EQ-5D have been the most commonly used instruments in clinical trials to assess the efficacy of treatments, such as gabapentin in postherpetic neuralgia 175 , diabetic polyneuropathy 176 and neuropathic pain due to peripheral nerve injury 170 ; the efficacy of duloxetine in diabetic peripheral neuropathy 177 ; and the efficacy of spinal cord stimulation in diabetic polyneuropathy 178 .…”
Section: Quality Of Lifementioning
confidence: 99%